The United States Army Aeromedical Research Laboratory Multi-Attribute Task Battery - Vogl, Jonathan; McCurry, Charles D.; Bommer, Sharon; Atchley, J. Andrew (Frontiers in Neuroergonomics, 2024)
The U.S. Army Aeromedical Research Laboratory (USAARL) Multi-Attribute Task Battery (MATB) represents a significant advancement in research platforms for human performance assessment and automation studies. The USAARL MATB builds upon the legacy of the traditional MATB, which has been refined over 30 years of use to include four primary aviation-like tasks. However, the USAARL MATB takes this foundation and enhances it to meet the demands of contemporary research, particularly in the areas of performance modeling, cognitive workload assessment, adaptive automation, and trust in automation. The USAARL MATB retains the four classic subtask types from its predecessors while introducing innovations such as subtask variations, dynamic demand transitions, and performance-driven adaptive automation handoffs. This paper introduces the USAARL MATB to the research community, highlighting its development history, key features, and potential applications.